The Effect of Leverage on Company Value with Dividend Policy as a Mediating Variable and Business Risk as a Moderating Variable - Shinta Rizki Septiani; Fauji Sanusi; Enis Khaerunnisa (Institute of Advanced Knowledge and Science, 2024)
This study aims to find out the effect of leverage on company value mediated by dividend policy and moderated by business risk in infrastructure sector companies listed on the IDX in the period 2017 – 2022. The research uses a quantitative method using secondary data from the financial statements of each company, both obtained through the IDX website and the official website of each company. Sampling uses a non-probability method on companies listed in the infrastructure sector listed on the IDX in 2017-2022. The research data is panel data analyzed using SPSS and Hayes Process with analysis stages, namely descriptive statistics to conditional process analysis. The results of the hypothesis test show that leverage has a negative and significant effect on the company's value, Dividend Policy has a positive and significant effect on the company's value, Leverage has no effect on the dividend policy, Dividend policy is unable to mediate the influence of leverage with the company's value, Business Risk is unable to moderate the influence of leverage with the dividend policy and Business Risk is able to moderate the influence of leverage with the company's value.